Diversity of Plant Species in Moringa-Based Homestead of Jaintiapur Upazila in Sylhet District - Prova, S J; Ahsan Talucder, Mohammad Samiul; Uddin, Md Sharaf (SAARC Journal of Agriculture, 2023)
Homestead agroforestry is crucial for food, fiber, and other necessities which are required outside the conventional forests. Thus, homestead agroforestry meets the criteria for a sustainable forest management scheme, providing a better way for biodiversity conservation. Moringa based homestead agroforestry in Sylhet has an opportunity to encourage species diversity for its various structural properties. This paper explores the plant species diversity of Moringa based homestead area at Jaintiapur upazila in Sylhet. Personal interviews were conducted from June 2022 to September 2022 with 40 randomly selected respondents who were involved in Moringa-based homestead agroforestry. Shannon-Wiener Diversity Indices (SWDI) was used to explore the plant species diversity index. In the study area identified plant species were 50.0% fruits, 26.3% vegetables, 15.8% timber and 7.9% medicinal plants. Among all the plant species, the higher diversity was found in fruit species followed by timber species, vegetable species and medicinal species. Most of plant species were found in boundary side of homestead area. Vegetable plant diversity was found high (Hʹ = 0.94-0.72), fruit species was also high (Hʹ = 0.99-0.69), medicinal species was medium to high (Hʹ = 0.62-0.97) and timber plant species was high (Hʹ =0.86-0.94) in different homestead areas. It may be concluded that plant species diversity as observed in Moringa based homestead area could be a good option for biodiversity conservation in Sylhet area of Bangladesh. SAARC J. Agric., 21(2): 119-129 (2023)